Evaluation of Fungicide Programs Against Phomopsis Leaf Blight on Eggplant - Anthony P. Keinath; Sierra H. Zardus (Plant Health Progress, 2026)
Phomopsis blight caused by the fungus Diaporthe vexans is commonly found on eggplant ( Solanum melongena) leaves, stems, and fruits in the fall growing season in the southeastern United States. The aim of this study was to determine which of 10 fungicides currently registered on eggplant are effective against Phomopsis leaf blight. Field experiments were performed in the fall of 2023, 2024, and 2025 with 10 fungicides applied preventatively before plants were inoculated with conidial suspensions of D. vexans. Chlorothalonil was used as the rotation partner with fungicides that required applications to be alternated with a different active ingredient. Plants treated with mefentrifluconazole (Cevya, Fungicide Resistance Action Committee [FRAC] code 3), cyprodinil + difenoconazole (Inspire Super, FRAC 9 + 3), or difenoconazole + benzovindiflupyr (Aprovia Top, FRAC 3 + 7), each rotated with chlorothalonil (Bravo Weather Stik, FRAC 05), had significantly less foliar necrosis than the water control in 2023 and 2025; these three treatments did not differ significantly from one another. Pyraclostrobin + fluxapyroxad (Priaxor, FRAC 11 + 7) also reduced foliar necrosis in 2023. Pyraclostrobin (Cabrio, FRAC 11) and boscalid (Endura, FRAC 7), both rotated with chlorothalonil, and chlorothalonil, chlorothalonil + zoxamide (Zing!, M05 + 22), copper oxychloride + copper hydroxide (Badge X2, FRAC M01), and chlorothalonil + cymoxanil (Cymbol Advance FRAC M05 + 27) were ineffective. The results of this study can be used to refine fungicide recommendations to manage Phomopsis blight on eggplant in the United States.